Identification of candidate blood biomarkers through metabolomics analysis in bovine superovulation - Su, Xiaohu; Gao, Guangqi; Chen, Liqiang; Zhang, Liguo; Liu, Guangnan; Bian, Chao; Su, Guanghua; Yang, Lei (Frontiers in Veterinary Science, 2025)
Superovulation and embryo transfer technologies provide strong support for improving the productivity of cattle population. A non-invasive diagnostic method for superovulation prediction is necessary to improve its efficiency. Compared to macromolecular substances, there has been an increasing number of studies on small molecular metabolites as biomarkers. This study aimed to identify key biomarkers associated with superovulation outcomes in cows through serum metabolomics analysis. In this study, 36 induced estrus cows were selected, and the blood samples were collected at three time points: before FSH injection, before artificial insemination, and before embryo collection. Then, the cows were classified into high embryonic yield (HEY) and low embryonic yield (LEY) groups based on the total number of embryos. Furthermore, a serum untargeted metabolomics analysis of the two groups was conducted using liquid chromatography with tandem mass spectrometry (LC–MS/MS). A total of 372 embryos were collected. The metabolomics analysis revealed that 1,158 metabolites were detected, and 617 were annotated. In the before FSH injection samples, 121 differential metabolites were identified between the two groups. In the before artificial insemination samples, 129 differential metabolites were identified. In the before embryo collection samples, 201 differential metabolites were identified. A total of 11 differential metabolites were shared between the before FSH injection and before artificial insemination samples, while five differential metabolites were shared across all three samples. The majority of the differential metabolites were significantly enriched in pathways related to amino acid and fatty acid metabolism, digestive system secretion, and ovarian steroidogenesis. This study showed that phosphatidylcholine [PC; 14:0/22:1(13Z)], phosphatidylethanolamine [PE; DiMe (11, 3)], triacylglycerol [TG; 15:0/16:0/22:4 (7Z, 10Z, 13Z, 16Z)], phosphatidylinositol [PI; 16:0/22:2 (13Z, 16Z)], and phosphatidylserine [PS; 18:0/20:4(8Z, 11Z, 14Z, 17Z)] were differentially expressed in the serum during the superovulation period. These could serve as potential biomarkers for embryonic yield prediction in bovine superovulation. The lipid and amino acid metabolic pathways may have an impact on the ovarian response. The results of this study could provide novel screening indexes of donors for bovine superovulation, although the accuracy of the relevant factors requires further investigation.